PERANAN GURU DALAM MEMANFAATKAN SD NEGERI 110 KELURAHAN SIDOMULYO BARAT KECAMATAN TAMPAN PEKANBARU - Fresdian, Widhia Sukma; Maemunaty, Titi; ', Widiastuti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : This reaserch is motivated by the lack of the teachers’ role in the use of the library so that the interest of the students less to visit the library of SDN 110 Pekanbaru. Based on the background above, the reaserch problem can be formulated as follow : how is the role of teachers in the use of the library of SDN 110 Pekanbaru?. The aim of this reaserch is to find out the role of teachers in the use of the library of SDN 110 Pekanbaru. The subject of this reaserch is 4 people who are also as the informan to get the information and data about the role of the teachers in the use of library. The data is analyzed by using descriptive analysis of case study and the approach is qualitative. Based on the interview and the observation, the writer finds out that the role of the teachers as the facilitators is already good enough which can be seen from the books, the comfortable room, and also the tools that support the learning process.Next is as the moderator, the teachers have done it well by giving the advice to the students. Not only as the moderator, the role of teachers as the motivator is also good by making a contest and reward to the students, the last role is as the evaluator, the teachers have done it well too by scoring the students as individual and also as the group. So it can be concluded that the four roles of the teachers in the use of library have been implemented properly.Key words: Reaserch is motivated by the lack of the teacher role in the use of the library.